2020
DOI: 10.1186/s12957-020-01846-3
|View full text |Cite
|
Sign up to set email alerts
|

MiR-489 inhibited the development of gastric cancer via regulating HDAC7 and PI3K/AKT pathway

Abstract: Background: Mounting evidences have displayed that the dysregulation of miRNAs plays important roles in the pathogenesis of gastric cancer (GC). The purpose of this study was to explore the biological functions and potential mechanism of miR-489 in GC progression. Methods: Quantitative real-time PCR (qRT-PCR) and western blot were performed to examine the mRNA expression and protein levels of miR-489 and HDAC7. The relationship between miR-489 and HDAC7 was analyzed by Spearman rank correlation. 3-(4,5-dimethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…It is worth noting that previous studies have identified multiple lncRNAs and miRNAs with critical functions in EC and other cancers [20][21][22][23][24][25][26]. Future studies should focus on the clinical applications of these lncRNAs and miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that previous studies have identified multiple lncRNAs and miRNAs with critical functions in EC and other cancers [20][21][22][23][24][25][26]. Future studies should focus on the clinical applications of these lncRNAs and miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…RNAs are also involved in the development of gastric cancer. For example, miR-489 overexpression can inhibit the survival, invasion, and migration of gastric cancer cells, and circulating lncRNAs play an important role in the early diagnosis of GC [ 34 , 35 ]. Furthermore, the clinical results of gastric cancer can be predicted by constructing nomogram [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, calcium release-activated calcium modulator 2 mediated store-operated calcium activity and promoted gastric cancer tumorigenic properties through the activation of the PI3K/Akt signaling pathways [ 25 ]. miR-489 functions as an oncogene can significantly promote GC cell (SGC7901 and MKN45) proliferation, invasion, and migration and effectively block the activation of PI3K/AKT pathway [ 26 ]. Yu et al found that Zi Yin Hua Tan (ZYHT) recipe could inhibit tumor growth and cell proliferation and promote apoptosis in gastric cancer by suppressing the PI3K/AKT pathway [ 27 ].…”
Section: Discussionmentioning
confidence: 99%